Correlation Study of Thyroid Disorders in Patients with Diabetes Mellitus (Type I and II) from Pakistan - Akhtar, Mehnaz; Mehboob, Sumaira; Bakhsh, Ahmed; Ur-Rehman, Kashif (Journal of Basic and Emerging Sciences, 2024)
Diabetes mellitus and thyroid hormonal imbalance are the two most common endocrine disorders which run parallel in clinical pattern due to malfunctioning of insulin hormone and thyroid hormones. Diabetes mellitus (DM) is the most prevailing carbohydrate metabolic disorder where 463 million adults suffering with type 2 diabetes. This study comprised a survey of thyroid disorders of diabetic subjects and the estimation of thyroid hormones including triiodothyronine T3, thyroxine T4 and thyroid stimulating hormones TSH in diabetic patients and their comparison with healthy controls. The study group consisted of 100 diabetic patients with mean age 45 years (± 10.5), mean height 166 cm (± 10.42) and average weight 70 kg (± 16.9). 40 healthy subjects without these endocrine disorders were selected as controls. For study purpose diabetic patients were divided in three groups having type I, type II diabetes and non-diabetic controls. The status of diabetes and thyroid function status including hyperthyroidism and hypothyroidism was analyzed by study performa along with other facts like age, gender, body mass index, blood pressure etc. among study participants. The study showed that both disorders were correlated with each other where diabetic females were at high risk of thyroid dysfunction. This study demonstrates the positive correlation of both endocrine disorders in our local community which would help the clinicians in treatment of patients suffering with health issues.